Risk tolerance dan niat investasi berisiko di kalangan mahasiswa: Peran literasi keuangan sebagai variabel moderasi - Juwono, Angela; Tan, Felice Carmelite Aprilie; Sudarsono, Jethson Edbert; Anastasia, Njo (Nur Science Institute, 2025)
Various factors influence the decision-making process in investment. This study examines the effect of risk tolerance on risky investment intention among university students, with financial literacy as a moderating variable. A quantitative causal approach was employed, using questionnaires distributed via Google Forms. The research sample consisted of 100 university students selected through purposive sampling. Data analysis was conducted using SmartPLS 4.0. The results indicate that risk tolerance significantly influences risky investment intention, whereas financial literacy does not significantly affect risky investment intention. Financial literacy does not moderate the relationship between risk tolerance and risky investment intention. A high level of financial literacy does not necessarily ensure a person's willingness to engage in risky investments. Other factors, such as prior investment experience and psychological factors influence investment decisions. Individuals must understand and manage their emotions and evaluate risk tolerance levels to make wiser investment decisions.